How gay men prepare for death : the dying business - Robinson, Peter (Emerald Publishing Limited, 2023)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online. How do we prepare for the penultimate stage of life? This is a crucial question now facing the ageing post-war generation. Examining research participants' use of wills, guardianship, medical attorney and beneficiaries, as well as their funeral plans and how they envisage the physical end of life, Peter Robinson's new book provides a practical contribution for anyone considering how to prepare for their end of life, including those from LGBTQ+ communities. Drawing on theory where appropriate, Robinson focuses on the practicalities of end-of-life preparation as revealed through a variety of personal experiences. With its universal application and international scope, How Gay Men Prepare for Death: The Dying Business supports the work of carers, charities and policymakers, and benefits readers from all backgrounds, as well as those from LGBTQ+ communities.